Empowering communities to co-manage watersheds: Forum for citizen action - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Community participation is recognized as an essential part of equitable and sustainable watershed management. Stakeholders play a vital role in ensuring that land use in the upstream does not affect the quality and quantity of water that flows to downstream communities. Regulatory measures could potentially address this concern. However, they entail high monitoring costs and compliance is not certain. In theory, stakeholder participation in watershed management can be a solution to these challenges.